2017
DOI: 10.1111/wrr.12602
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix/stromal vascular fraction gel conditioned medium accelerates wound healing in a murine model

Abstract: Conditioned medium (CM) is a new treatment modality in regenerative medicine and has shown a successful outcome in wound healing. We recently introduced extracellular matrix/stromal vascular fraction gel (ECM/SVF-gel), an adipose-derived stem cell and adipose native extracellular matrix-enriched product for cytotherapy. This study aimed to evaluate the effect of CM from ECM/SVF-gel (Gel-CM) on wound healing compared with the conventional CM from adipose tissue (Adi-CM) and stem cell (SVF-CM). In vitro wound he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…For instance, ECM has been shown to play an important role in the regulation of stem cells and different ECM in ex vivo culture system can result in the differential expression of genes [23]. For example, 3D Matrigel has been shown to support the stemness of LNC better than coated Matrigel [3], and the conditioned medium containing ECM components promoted wound healing of mice skin [24]. Some ECM components that may plan a vital role include EGFL6 and FBLN1.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ECM has been shown to play an important role in the regulation of stem cells and different ECM in ex vivo culture system can result in the differential expression of genes [23]. For example, 3D Matrigel has been shown to support the stemness of LNC better than coated Matrigel [3], and the conditioned medium containing ECM components promoted wound healing of mice skin [24]. Some ECM components that may plan a vital role include EGFL6 and FBLN1.…”
Section: Discussionmentioning
confidence: 99%
“…They recently demonstrated that ECM/SVF-gel exhibited greater effects on wound healing compared with SVF suspension, mainly as a result of the high concentration of growth factors secreted by the ECM/SVF-gel [20]. Furthermore, CM from ECM/SVF-gel was rich in growth factors and improved wound healing compared with conventional SVF-CM [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fat-derived products vary between conventional CF, CAL, and mechanically processed fat grafts such as SVF gel. Because CF has been extensively applied, many fat-derived products have been developed to condense ASCs for not only improved volume retention, but also for improved therapeutic e cacy in wound healing and skin diseases [27,31]. CAL attaches ASCs to the aspirated fat, converting ASC-poor aspirated fat to ASC-rich fat [32].…”
Section: Discussionmentioning
confidence: 99%